Does trade matter for stock market integration? - Abdul Karim, Bakri; Abd. Majid, M. Shabri (Emerald Group Publishing Limited, 2010)
Purpose – The purpose of this paper is to re-examine the stock market integration and short-run dynamic interactions between the Malaysian stock market and the stock markets of its major trading partners (the USA, Japan, Singapore, China and Thailand).